2013
DOI: 10.1586/1744666x.2013.836450
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing wheeze phenotypes to identify endotypes of childhood asthma, and the implications for future management

Abstract: It is now a commonly held view that asthma is not a single disease, but rather a set of heterogeneous diseases sharing common symptoms. One of the major challenges to treating asthma is understanding these different asthma phenotypes and their underlying biological mechanisms.This review gives an epidemiological perspective of our current understanding of the different phenotypes that develop from birth to childhood that come under the umbrella term "asthma". The review focuses mainly on publications from long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 89 publications
0
44
1
Order By: Relevance
“…36 The age at which a child initially wheezes has been described as a key discriminator of childhood wheeze phenotypes in multiple birth cohort studies, and our results which identified an early-onset and a late-onset asthma subtype are consistent with other previously published work. 20,21,37 However, unlike most previous studies, we identified both an early-onset non-atopic subtype and an early-onset atopic subtype.…”
Section: Discussioncontrasting
confidence: 95%
“…36 The age at which a child initially wheezes has been described as a key discriminator of childhood wheeze phenotypes in multiple birth cohort studies, and our results which identified an early-onset and a late-onset asthma subtype are consistent with other previously published work. 20,21,37 However, unlike most previous studies, we identified both an early-onset non-atopic subtype and an early-onset atopic subtype.…”
Section: Discussioncontrasting
confidence: 95%
“…Most genetic studies defined "asthma" as parentally or patient-reported "doctor-diagnosed asthma". Unless genetic studies find better ways to distinguish between different asthma subtypes under this umbrella diagnosis at a population level, it will be difficult (if not impossible) to discover their unique underlying genetic risk factors, as any signal will be diluted by phenotypic heterogeneity [83]. It is worth emphasizing that when a much more precise and specific definition of early-life onset asthma with recurrent, severe exacerbations in pre-school age was used in a GWAS, identified associations had a considerably greater effect size (e.g.…”
Section: Asthma Phenotypes and Genetic Studiesmentioning
confidence: 99%
“…The concept of asthma endotypes has now been the subject of much research because endotypes address the underlying mechanism of a disease [17][18][19][20]. However, this is also confusing because of the highly redundant inflammatory pathways that can lead to disease.…”
Section: Severe Asthma-many Diseases Many Problemsmentioning
confidence: 99%
“…Ultimately, asthma, like many other diseases, is a heterogeneous disease with many phenotypes and endotypes [17,18]. Not one single treatment will fit all, and the art of medicine may be to find the right peg for the corresponding hole [22].…”
Section: Severe Asthma-many Diseases Many Problemsmentioning
confidence: 99%